2017
DOI: 10.3727/096504016x14774889687280
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Protein D52 (TPD52) Inhibits Growth and Metastasis in Renal Cell Carcinoma Cells Through the PI3K/Akt Signaling Pathway

Abstract: Tumor protein D52 (TPD52) is a member of the TPD52-like protein family and plays different roles in various types of malignancies. However, its role in renal cell carcinoma (RCC) is still unclear. In this study, we investigated the role of TPD52 in RCC. The mechanism of TPD52 in RCC was also investigated. Our data demonstrated that the expression levels of TPD52 in both mRNA and protein were significantly decreased in RCC cells. Overexpression of TPD52 inhibited proliferation, migration, and invasion with decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Moreover, accumulating evidence revealed that TPD52 was involved in cellular transformation, proliferation, apoptosis, and metastasis. 40,41 Yang et al demonstrated that knockdown of TPD52L2 (a member of the TPD52) suppressed the proliferation and colony formation in BC cells. 42 Zhang et al found that TPD52 expression was markedly increased in BC tissues and cells, and deficiency of miR-449 promoted proliferation and metastasis of BC cells through regulating TPD52.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, accumulating evidence revealed that TPD52 was involved in cellular transformation, proliferation, apoptosis, and metastasis. 40,41 Yang et al demonstrated that knockdown of TPD52L2 (a member of the TPD52) suppressed the proliferation and colony formation in BC cells. 42 Zhang et al found that TPD52 expression was markedly increased in BC tissues and cells, and deficiency of miR-449 promoted proliferation and metastasis of BC cells through regulating TPD52.…”
Section: Discussionmentioning
confidence: 99%
“…To a further extent, PI3K/AKT/mTOR is identified as a highly enriched pathway in translocation RCC with TFE3 fusion (TFE3-tRCC) by miRNA microarray analysis [258]. Besides that PIK3R1 regulates EMT and stem-like phenotype of RCC cells through the AKT/GSK3β/CTNNB1 pathway [259], FoxO, PKCε, TPD52, NOTCH1, ETS2, miR-19b, -122, -182, -193a-3p, -195, and -224, as well as LncRNA MALAT1, TP73-AS1 and HOTTIP modulate proliferation, apoptosis, invasion, metastasis, or EMT via PI3K/ AKT pathway [260][261][262][263][264][265][266][267][268][269][270][271][272]. However, only a few of clinical trials of PI3K/AKT inhibitors in touch try to offer hope for KC patients (Tables 2 and 3).…”
Section: Dysregulation Of the Pi3k/akt Pathway In The Genitourinary Smentioning
confidence: 99%
“…1). Thus, strong up-regulation was shown for BRCA1 and TPD52 genes, both of which act as tumor suppressors [21,24]. Moreover, BRCA1 participates in maintaining genomic stability, in ubiquitination of specific proteins and transcriptional regulation [21].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, BRCA1 participates in maintaining genomic stability, in ubiquitination of specific proteins and transcriptional regulation [21]. Tumor protein D52 inhibits growth and metastasis of renal cell carcinoma through the PI3K/ AKT signaling pathway since plays different roles in various types of malignancies [24]. Thus, our results concerning up-regulation of BRCA1 and TPD52 gene expressions in IRE1 knockdown cells agree well with the functional role of BRCA1 and TPD52 proteins and also with suppression of glioma cell proliferation after inhibition of IRE1 [4,21,24,28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation